Development of a competency-based curriculum for microbiology and parasitology for Philippine medical schools - Dotollo, Ma. Teresa K.; Nemuel S. Fajutagana MD MHPEd (2007)
The aim of every medical school is to produce competent physicians. The responsibility of every medical discipline, therefore, is to ensure that whatever is taught by their faculty members are based on competencies that are expected of their graduates. This study used a research and development design. The research phase employed the Delphi technique to elicit a consensus of opinions from three populations of stakeholders. Seven officers and senior members of the Philippine Academic Society for Microbiology and Parasitology, 23 academicians teaching these two subjects from various medical colleges in the country, 18 practicing clinicians not teaching these two subjects, and 97 postgraduate medical interns participated, to produce a listing of competencies and subject matter content for a curricular framework for the teaching of the subjects Microbiology and Parasitology in the Philippines. A total of 23 competencies, 97 subject matter items in Microbiology and 60 subject matter items in Parasitology were gathered. SPSS version 11 was used to analyze the goup means from the Delphi rounds using Oneway ANOVA. Based on the data results gathered, the course objectives for these two subjects were formulated and the subject matter content listing was then ranked by order of importance and relevance to the Philippine setting, to form a design with suggested general teaching learning activities and evaluation methods.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Nemuel S. Fajutagana MD MHPEd, Chair/Adviser; Lupe A. Abarquez BSN MHPEd, Reader/Critic; Ma. Cecilia D. Alinea MD MHPEd, Member; Jose Alvin P. Mojica MD MHPEd, Member; Prof Teresita de Guzman MSPH, Member.
Keywords: Competency-based education -- Curricula